2022
DOI: 10.1021/acssuschemeng.2c03184
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-Stable Peroxidase Mimics Based on Biological Metal–Organic Frameworks for Recyclable Scavenging of Hydrogen Peroxide and Detecting Glucose in Apple Fruits

Abstract: Enzyme mimics constitute a promising class of biocatalysts with potential applications in bioanalysis, biomedicine, etc. due to their high catalytic activity and substrate specificity, but they often suffer from low operational stability and difficulties in recyclable utilization. Herein, we adopted an acid–base treatment to create an efficient enzyme mimic material by taking advantage of biological metal–organic frameworks (BioMOFs) constructed of the Cu2+ ion and a plant growth regulator. The prepared deprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…To demonstrate the encapsulation of H 2 O 2 in H 2 O 2 @HSTC-1, the crystals were rinsed with catalase three times (5 ml each) to remove H 2 O 2 from the surface, and then treated with 3,3′,5,5′-tetramethyl-benzidine (TMB), a commonly used chromogenic agent for H 2 O 2 detection. 30,31 The results showed that HSTC-1 and H 2 O 2 @HSTC-1 barely changed in 30 minutes after the addition of TMB ethanol solution (400 μL, 0.2 M). By adjusting the pH value with buffer, the colour gradually changed from colourless to blue, and an obvious absorption peak appeared at 652 nm, while for HSTC-1 alone it did not.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the encapsulation of H 2 O 2 in H 2 O 2 @HSTC-1, the crystals were rinsed with catalase three times (5 ml each) to remove H 2 O 2 from the surface, and then treated with 3,3′,5,5′-tetramethyl-benzidine (TMB), a commonly used chromogenic agent for H 2 O 2 detection. 30,31 The results showed that HSTC-1 and H 2 O 2 @HSTC-1 barely changed in 30 minutes after the addition of TMB ethanol solution (400 μL, 0.2 M). By adjusting the pH value with buffer, the colour gradually changed from colourless to blue, and an obvious absorption peak appeared at 652 nm, while for HSTC-1 alone it did not.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the characteristics of low cost, high stability and excellent repeatability, artificial mimic enzymes have been widely explored for their great potential application ranging from medicine, food processing, environmental analysis, and biotechnology [1] . Various nanozymes have been verified to possess good peroxidase activity, such as metal oxides, [2] noble metal, [3] carbon nanomaterials, [4] metal‐organic frameworks [5] . The catalytic property of mimic enzymes is directly affected by composition, structure and morphology of nanomaterials [6] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Various nanozymes have been verified to possess good peroxidase activity, such as metal oxides, [2] noble metal, [3] carbon nanomaterials, [4] metal-organic frameworks. [5] The catalytic property of mimic enzymes is directly affected by composition, structure and morphology of nanomaterials. [6] Introducing heteroatoms, constructing heterojunction and dispersing in multi-dimensional materials are used in catalytic synergy, enhancement of adsorption capacity and acceleration of carrier transfer, enhancing the activity of mimic enzymes in previous works.…”
Section: Introductionmentioning
confidence: 99%
“…To date, different nanomaterials of transition-metal oxides and chalcogenides (Fe 3 O 4 , MoS 2 , CeO 2 , CuO, FeS 2 , etc. ), noble metals (Ag, Au, Pt, Pd), ,,, carbon nanomaterials, , and metal–organic frameworks (MOFs) have been found to possess intrinsic peroxidase-like activity. The peroxidase-like activity of these nanomaterials has been utilized successfully for the fabrication of low-cost colorimetric assays for the detection of various analytes including glucose, , H 2 O 2 , biothiols, and dopamine .…”
Section: Introductionmentioning
confidence: 99%